A budget-friendly integrating sphere for reliable quantum yield characterization of fluorescent solutions - Yordi Afiq Syahrizal; Septian Budiman; Deski Beri (Next Materials)
Absolute fluorescence quantum yield (Φf) is a fundamental parameter for characterizing the photophysical behavior of fluorescent materials. This study presents the development of a budget-friendly integrating sphere system for accurate Φf measurements in solution-phase samples. The 28 cm sphere was fabricated using resin-reinforced rubber and coated internally with white paint and barium sulfate (BaSO₄) to ensure diffuse reflectivity. The design includes orthogonal excitation and detection ports, a top-mounted sample holder, and a baffle placed to block direct optical paths between the excitation source and detector, thereby ensuring uniform light distribution. Φf measurements were performed on standard dyes (Rhodamine B, Eosin B, and 2’,7’-Dichlorofluorescein) and a nonstandard fluorescent sample (orange highlighter ink) using 405 nm and 532 nm laser excitation. Repeatability was confirmed with relative standard deviation (RSD) values mostly below 6 %, and the combined relative uncertainty was estimated at ±7 % based on GUM principles. The Φf values obtained for Rhodamine B (0.72 and 0.71), Eosin B (0.62 and 0.63), and 2’,7’-Dichlorofluorescein (0.90) showed good agreement with literature data, while the orange highlighter ink exhibited high Φf (0.90 and 0.89), comparable to commercial dyes. These findings confirm that the proposed budget-friendly integrating sphere provides accurate, reproducible, and reliable fluorescence quantum yield data, making it well-suited for use in teaching and resource-limited research laboratories.